ICD-11 Personality Disorders: A Psychodynamic Perspective on Personality Functioning - Blüml, Victor; Doering, Stephan (Frontiers in Psychiatry, 2021)
The new ICD-11 introduces a fully dimensional classification of personality disorders representing a fundamental change in personality disorder diagnosis with major implications for clinical practice and research. The new system centers on the evaluation of the severity of impairment in the areas of self and interpersonal functioning. This focus on personality functioning converges with long-standing psychoanalytic/psychodynamic conceptualizations of personality pathology. In a detailed conceptual analysis and review of existing empirical data, points of convergence and notable differences between major exponents of the psychodynamic tradition – object relations theory as developed by Kernberg and colleagues and the Operationalized Psychodynamic Diagnosis – and the ICD-11 system are critically discussed. Personality functioning can be considered to be the current “common ground” for the assessment of personality disorders and constitutes a considerable step forward in making personality disorder diagnosis both clinically meaningful and suitable for research purposes.